Celebrating Robin Watkins' 5th Birthday at Frances Kamp's Home - Watkins, Howard::::::::: (1987)
Robin Watkins blowing out #5 candle; Adam Watkins, Frances Kamp, Jerry Kamp and Christine Watkins Big blue 5 on top of toy carousel